Prevention of cerebral thromboembolism by oral anticoagulation with dabigatran after pulmonary vein isolation for atrial fibrillation: the ODIn-AF trial: original paper - Schrickel, Jan Wilko; Beiert, Thomas; Linhart, Markus; Luetkens, Julian A.; Schmitz, Jennifer; Schmid, Matthias; Hindricks, Gerhard; Arentz, Thomas; Stellbrink, Christoph; Deneke, Thomas; Bogossian, Harilaos; Sause, Armin; et al. (Clinical research in cardiology, 2023)
Long-term oral anticoagulation (OAC) following successful catheter ablation of atrial fibrillation (AF) remains controversial. Prospective data are missing. The ODIn-AF study aimed to evaluate the effect of OAC on the incidence of silent cerebral embolic events and clinically relevant cardioembolic events in patients at intermediate to high risk for embolic events, free from AF after pulmonary vein isolation (PVI).